ALGEBRAIC REPRESENTATION ON SLICE OF MANDAR’S TYPICAL PASO CAKE SHAPE USING THE GEOGEBRA APPLICATION - Fitriani; Aras, Andi; Buhaerah (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to analyze algebra representations in the form of Mandar's typical paso cake slices by utilizing the GeoGebra application. The research method used is a qualitative approach with descriptive analysis with ethnographic design that involves observation and interviews with certain Mandar tribal communities. The results of this study provide further information to the Mandar people that there is a relationship between mathematics and their culture. In addition, the paso cake object enriches students' learning experience through the integration of local culture in mathematics learning and shows that the use of GeoGebra not only improves students' understanding of the concept of cone slices but can also improve the algebraic representation ability of geometry more easily. This research is expected to contribute to improving students' understanding of mathematical concepts through interactive and effective visualization in improving students' mathematical representation skills as well as the development of more contextual and relevant mathematics learning methods